2019
DOI: 10.1177/2050312119838746
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between patients’ and pharmacists’ perceptions of the role of community pharmacists as advisors on the use of pharmaceuticals in Japan: A comparison prior to and following revision of the Pharmacists’ Act

Abstract: Objectives:In 2014, immediately prior to the revision of Article 25-2 of the Pharmacists’ Act, we conducted a survey on pharmacists’ and patients’ perceptions of pharmacists’ roles. A role discrepancy between the two was identified. The objective was to examine changes in role perceptions and awareness of pharmacists as medication specialists following revision to the Pharmacists’ Act.Methods:The survey was conducted using an Internet-based questionnaire. A total of 469 patients and 354 pharmacists responded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…As regards our factor analysis, all three items mentioned in the previous paragraph were loaded in the "medicinal advice" factor, which consequently emerges as the Achilles heel of EOPYY pharmacies. Exactly the same failure has been previously reported for the Japanese community pharmacies, the users of which were found to expect their pharmacists to monitor changes in their lifestyles and provide clear explanations in order to rate them highly as medication specialists [23]. This restricted advisory role may be attributable to time pressure [24], but enhancing the advisory role would reasonably require even more time to be spent on each single patient.…”
Section: Discussionmentioning
confidence: 55%
“…As regards our factor analysis, all three items mentioned in the previous paragraph were loaded in the "medicinal advice" factor, which consequently emerges as the Achilles heel of EOPYY pharmacies. Exactly the same failure has been previously reported for the Japanese community pharmacies, the users of which were found to expect their pharmacists to monitor changes in their lifestyles and provide clear explanations in order to rate them highly as medication specialists [23]. This restricted advisory role may be attributable to time pressure [24], but enhancing the advisory role would reasonably require even more time to be spent on each single patient.…”
Section: Discussionmentioning
confidence: 55%
“…[11][12][13][14] Furthermore, SEM analysis is often utilized in pharmaceutical practice. 15,16) For instance, Yamamura et al found via SEM analysis, that pharmacists qualified to assess the pain status of patients contributed to improving the QOL of cancer patients. 15) Oshima et al revealed discrepancies in perceptions between patients and pharmacists regarding the use of pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…15,16) For instance, Yamamura et al found via SEM analysis, that pharmacists qualified to assess the pain status of patients contributed to improving the QOL of cancer patients. 15) Oshima et al revealed discrepancies in perceptions between patients and pharmacists regarding the use of pharmaceuticals. 16) However, SEM is yet to be applied to the manufacturing process of pharmaceutical products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation